Enantioselective Kinetic Resolution/Desymmetrization of Para‐Quinols: A Case Study in Boronic‐Acid‐Directed Phosphoric Acid Catalysis. Issue 2 (24th September 2019) - Huang, Banruo; He, Ying; Levin, Mark D.; Coelho, Jaime A. S.; Bergman, Robert G.; Toste, F. Dean
Abstract: A chiral phosphoric acid‐catalyzed kinetic resolution and desymmetrization of para ‐quinols operating via oxa‐Michael addition was developed and subsequently subjected to mechanistic study. Good to excellent s ‐factors/enantioselectivities were obtained over a broad range of substrates. Kinetic studies were performed, and DFT studies favor a hydrogen bonding activation mode. The mechanistic studies provide insights to previously reported chiral anion phase transfer reactions involving chiral phosphate catalysts in combination with boronic acids. Abstract :